(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This study aims to develop a system of criteria and indicators for identifying and assessing students’ linguistic competence within the framework of the CLIL (Content and Language Integrated Learning) approach. In the context of modern integrative education, the inextricable link between language and content complicates the assessment process, which indicates the inadequacy of traditional assessment approaches. Therefore, the study systematically analyzes the main components of linguistic competence - lexical, grammatical, phonological, discursive and pragmatic competencies. The research methodology uses theoretical analysis, componentization, modeling and empirical observation methods. As a result, a system of assessment criteria and indicators is developed that is suitable for the CLIL environment, accurate and focused on practical application. This system allows for a comprehensive assessment of students’ language knowledge not only in terms of grammatical accuracy, but also in terms of their ability to use it in a communicative and academic context. The developed system of criteria and indicators increases the objectivity of the assessment process, serves to more deeply identify students’ language skills, and ensures the effectiveness of education in CLIL classes. This approach also allows teachers to monitor the dynamics of individual student development and adjust the educational process.